PENGARUH EFIKASI DIRI TERHADAP PRESTASI BELAJAR SISWA DI SMA NEGERI SE-KECAMATAN NAMLEA - Syafa Lisaholit; Siti Hajar Loilatu; M Chairul Basrun Umanailo (Academy of Education Journal, 2021)
The Effect of Self-Efficacy, Learning Activities and Learning Independence on Biology Learning Achievement in Class X Students of Public Senior High Schools in Namlea District.The formulation of the problem in this study is how the effect of self-efficacy on student achievement in high school students in Namlea sub-district. This study aims to determine the effect of self-efficacy on the learning achievement of biology class X students in Namlea district. This type of research is ex-post facto which is causality designed to explain the existence of a causal relationship between variables. The population in this study amounted to 603 students of State Senior High School in Namlea district. The sample in this study amounted to 90 students. The data analysis technique used simple linear regression analysis.The results of the analysis show that self-efficacy has a positive and significant effect on the biology learning achievement of class X SMA Negeri in Namlea sub-district. Judging from the results of simple linear regression calculations, it can be seen that the magnitude of the influence is 0.271.While the R square value is 0.036. So it can be seen that the relative contribution of the effect of self-efficacy on learning achievement is 36.0%, while 64% is influenced by other variables not examined in the study.